Identification of nonpoint source pollution source/sink in a typical watershed of the Three Gorges Reservoir Area, China: A case study of the Qijiang River. (1st January 2022) - Tan, Shaojun; Xie, Deti; Ni, Jiupai; Chen, Fangxin; Ni, Chengsheng; Shao, Jing'an; Wang, Jinliang; Zhu, Dun; Wang, Sheng; Lei, Ping; Wang, Jingyi; Xu, Jianfeng
Abstract: Constructing a simple and accurate method to identify the risks and control nonpoint source pollution (NPSP) have become a principal target for the most watersheds with strong soil erosion and agricultural activities all over the world. In this study, the Qijiang River Basin in the Three Gorges Reservoir area (TGRA) was selected as the study area and the minimum cumulative resistance (MCR) surface method and location-weighted landscape index (LWLI) were used to identify the source/sink pattern of the NPSP. The results from MCR modeling showed that the source landscape mainly distributed in the northern hilly area near the Yangtze River mainstream, however, the sink landscape mainly concentrated in the southern Simian Mountain area. The LWLI values in the north were higher than those in the south. Regression analysis showed that there is a significant correlation between the LWLI and soil erosion ( R 2  = 0.635); meanwhile, there was also a certain relationship between the LWLI and water quality in the dry and wet seasons, ammonia nitrogen (NH3 –N) and total phosphorus (TP) was the largest. The correlation coefficient between the chemical oxygen demand (COD) and NH3 –N in the wet season was greater than that in the dry season, while total nitrogen (TN) and TP are exactly the opposite. The research results can help the areas with fragmented landscape, easy soil erosion, high agricultural activity, and lack of monitoring data to identify the risk of agricultural NPSP and formulate scientific water resources protection measures. Highlights: Resistance/power factor system was improved to identify source/sink landscape. LWLI was adopted to identify the source/sink of NPSP. Source mainly distributed in the north, and sink concentrated in the south. The methods could promotes to sustainable environment development in TGRA.